The Modernist Legacy: Essays on New Music - Heile, Björn (Farnham Ashgate, 2009)
This collection of essays offers a historical reappraisal of what musical modernism was, and what its potential for the present and future could be. It thus moves away from the binary oppositions that have beset twentieth-century music studies in the past, such as those between modernism and postmodernism, between conceptions of musical autonomy and of cultural contingency and between formalist-analytical and cultural-historical approaches. Focusing particularly on music from the 1970s to the 1990s, the volume assembles approaches from different perspectives to new music with a particular emphasis on a critical reassessment of the meaning and function of the legacy of musical modernism. The authors include scholars, musicologists and composers who combine culturally, socially, historically and aesthetically oriented approaches with analytical methods in imaginative ways.While the depiction of musical modernism that emerges is on the whole more positive than what has been prevalent in recent musicological discussions, this does not mean that the contributors are unanimous or uncritical. On the contrary, there is a considerable variety of viewpoints, including critiques of aspects of modernism, at times undertaken from positions that could be described as postmodernist. It is this kind of critical debate on modernism that the book intends to foster.
Modernism's Moment of Plenitude / Andrew Timms -- Fields of Rubble: On the Poetics of Music after the Postmodern / John Croft -- Spectralism, Politics and the Post-Industrial Imagination / Eric Drott -- The Scream in Avant-Garde Music: The New Left and the Rediscovery of the Body / Beate Kutschke -- Verbal Discourse as Aesthetic Arbitrator in Contemporary Music -- Weltmusik and the Globalization of New Music / Björn Heile -- Temps perdu: Aldo Clementi and the Eclipse of Music as Praxis / David Osmond-Smith -- Feldmann-Beckett-Johns: Patterning, Memory and Subjectivity / Catherine Laws -- Brian Ferneyhough, 'Postmodern Modernist' / Lois Fitch -- The Electroacoustic Music of Henri Pousseur and the 'Open' Form / John Dack -- Self-Portrait with Boulez and Machaut (and Ligeti is there as well): Harrison Birtwistle's Hoquetus Petrus / Mark Delaere -- Local Polymetric Structures in Elliott Carter's 90+ for Piano (1994) / Ève Poudrier
Keywords: Clementi, Aldo; Feldman, Morton -- 1926-1987; Beckett, Samuel -- 1906-1989; Johns, Jasper -- -1930; Ferneyhough, Brian -- 1943-; Pousseur, Henri -- 1929-2009; Birtwistle, Harrison -- -1934; Carter, Elliott -- 1908-2012; 20th Century (1901-2000); 21st Century (2001-2100); Musical analysis